2014
DOI: 10.1002/2013jd020752
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of monsoon low-level jet observed over an Indian tropical station during the peak monsoon period from high-resolution Doppler wind lidar measurements

Abstract: Doppler wind lidar measurements of horizontal winds at an Indian tropical station, Mahbubnagar (16.73°N, 77.98°E, 445 m above mean sea level), were used to investigate the time evolution of the monsoon low-level jet (MLLJ) during the southwest monsoon season. Vertical profiles of zonal wind in the altitude range of 100 to 3000 m above surface (at every 50 m height interval and 5 min time averaged) obtained during the period 25 July to 23 August 2011 are considered for the analysis. The zonal winds in the altit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 52 publications
1
12
0
3
Order By: Relevance
“…An analysis of the diurnal variations of MLLJ during the individual monsoon months (Figure S5) indicates that the strength of the MLLJ is higher and exhibits larger diurnal variations during the peak monsoon months of July and August than in June and September. The influence of the pressure gradient and the resulting large‐scale southwesterly flow is stronger during the daytime, while the effect of mountain gaps is predominant during night‐time where the secondary flow of the MLLJ winds is found to be stronger (Ruchith et al ., ; Du et al ., ). The diurnal changes in the winds can alter the humidity gradients in the LLJ outflow region, which then triggers moisture convergence and favours the formation of convection systems (Chen and Tomassini, ).…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the diurnal variations of MLLJ during the individual monsoon months (Figure S5) indicates that the strength of the MLLJ is higher and exhibits larger diurnal variations during the peak monsoon months of July and August than in June and September. The influence of the pressure gradient and the resulting large‐scale southwesterly flow is stronger during the daytime, while the effect of mountain gaps is predominant during night‐time where the secondary flow of the MLLJ winds is found to be stronger (Ruchith et al ., ; Du et al ., ). The diurnal changes in the winds can alter the humidity gradients in the LLJ outflow region, which then triggers moisture convergence and favours the formation of convection systems (Chen and Tomassini, ).…”
Section: Resultsmentioning
confidence: 99%
“…During monsoon months, westerly/southwesterly winds prevail over the region. Ruchith et al [] observed wind lidar‐derived vertical distribution of zonal winds over the region. They found that the upward lift of the core of westerly maximum wind speed after the local sunrise is due to the growth of the convective boundary layer, and during the late afternoon it collapsed to lower levels.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the speed of the LLJ increases, particularly around 950–925 hPa, because the strong low‐level southeasterly wind from the Bay of Bengal can flow over the flat lowland without being slowed down greatly by surface friction. The inertial oscillation can also enhance the nocturnal LLJ (Blackadar, ; Rife et al, ; Van de Wiel et al, ; Ruchith et al, ). The acceleration of the jet occurs above the neutrally stratified layer above 950 hPa.…”
Section: Discussionmentioning
confidence: 99%